2016
DOI: 10.1016/j.ajhg.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic Variants in UBA5 Reveal that Disruption of the UFM1 Cascade Can Result in Early-Onset Encephalopathy

Abstract: Via whole-exome sequencing, we identified rare autosomal-recessive variants in UBA5 in five children from four unrelated families affected with a similar pattern of severe intellectual deficiency, microcephaly, movement disorders, and/or early-onset intractable epilepsy. UBA5 encodes the E1-activating enzyme of ubiquitin-fold modifier 1 (UFM1), a recently identified ubiquitin-like protein. Biochemical studies of mutant UBA5 proteins and studies in fibroblasts from affected individuals revealed that UBA5 mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
130
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 90 publications
(142 citation statements)
references
References 34 publications
12
130
0
Order By: Relevance
“…Recently, we and Bonneau's group have independently shown that compound heterozygote for a loss‐of‐function mutation on one allele and a p.Ala371Thr mutation on the other causes severe infantile‐onset encephalopathy . We have also shown that the UBA5 A371T mutation suppresses the formation of UFMylated UFBP1 .…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Recently, we and Bonneau's group have independently shown that compound heterozygote for a loss‐of‐function mutation on one allele and a p.Ala371Thr mutation on the other causes severe infantile‐onset encephalopathy . We have also shown that the UBA5 A371T mutation suppresses the formation of UFMylated UFBP1 .…”
Section: Resultsmentioning
confidence: 88%
“…Heterozygotes with single loss‐of‐function allele do not show any disease symptom, implying that combination of functionally defect mutation with a loss‐of‐function is crucial for the disease onset. In addition to the p.Ala371Thr mutation, Bonneau's group identified individuals from two families with biallelic compound heterozygous variants in UBA5 , p.Met57Val, and p.Gly168Glu, and p.Val260Met and p.Asp389Tyr (Fig. A and B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That, therefore, suggests that modulating the stability of the UBA5 dimer can serve as a tool to regulate the UBA5 affinity to ATP. Indeed, recently, it has been found that the UBA5 mutation V260M, which affects UFMylation, is related to early onset encephalopathy (33). That mutation is located within the UBA5 dimer interface; therefore, based on our work, it has the potential to interfere with ATP binding.…”
Section: Discussionmentioning
confidence: 99%